Registration of 'Bobcat' hard red winter wheat. Issue 3 (22nd June 2020) - Bruckner, P. L.; Berg, J. E.; Lamb, P. F.; Kephart, K. D.; Eberly, J. O.; Miller, J. H.; Chen, C.; Torrion, J. A.; Pradhan, G. P.; Ramsfield, R.; Nash, D. L.; Holen, D. L.; et al.
Abstract: 'Bobcat' (Reg. no. CV‐1161, PI 693235) hard red winter (HRW) wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in September 2019. Bobcat is of unknown pedigree, derived from a composite of two related single crosses made in 2007: MT0598/98X366‐E29‐1 and 01X258‐C1/MT0598. MT0598 is an unreleased, hollow‐stem experimental line, and 98X366‐E29‐1 and 01X258‐C1 are unreleased, Montana solid‐stem experimental lines. Bobcat was developed using a modified bulk breeding method and selected as an F5:6 head row. Bobcat was tested under the experimental number MTS1588 from 2015 to 2019 in Montana. Quality was evaluated in multilocation Montana trials since 2015. Bobcat is a solid‐stem, high‐yielding HRW wheat cultivar with medium to high test weight, medium maturity, reduced height ( Rht‐B1b ), medium to high grain protein, and acceptable milling and baking quality. Bobcat was released for its improved host plant resistance to wheat stem sawfly ( Cephus cinctus Nort.) conditioned by stem solidness, along with short stature, and improved yield potential relative to 'Warhorse', the current predominant solid‐stem cultivar in Montana.